The Holistic Trinity: Community-based Faith Leaders, Black Canadians, and Counselors - Sraha-Yeboah, Michelle (Counseling and values, 2025)
In this qualitative study, interviews were conducted with 12 Black parish ministers of primarily Black congregations in Vancouver, Edmonton, and the Greater Toronto Area (gta). The objective was to examine how parish ministers cultivate mental wellness in their congregations and determine how these efforts may inform counselors’ mental healthcare service delivery for expressly religious Black Canadian communities. Applying Braun and Clarke’s (2022) reflexive thematic analysis to the interviews generated five key themes: (a) Mental healthcare as a holistic enterprise; (b) Healing in community for communal healing; (c) Creating a culture of collaboration; (d) Hope as a psychosocial resource and protective factor across generations; and (e) Black faith community leaders as mediators between Black community members and the police. The findings are discussed within a Black Feminist Psychology Framework (bfp). Implications for collaboration between parish-ministers and counselors are considered.